2019
DOI: 10.3390/ijerph16245127
|View full text |Cite
|
Sign up to set email alerts
|

The Impacts of Different Air Pollutants on Domestic and Inbound Tourism in China

Abstract: Previous studies have reported that air pollution negatively affects the tourism industry. This paper attempted to answer the following question: among different air pollutants, which one acts as the most adverse factor? The study was based on a sample of panel data covering 337 Chinese cities for the period between 2007 and 2016. Four pollutant indicators were inspected: PM 2 . 5 (particulate matter 2.5 micrometers or less in size), PM 10 (particulate matter 10 micrometers or less in size), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 54 publications
2
13
0
Order By: Relevance
“…Although the core finding of this study on the harmful influence of air pollution in China is qualitatively consistent with the findings of Dong et al [27], Xu et al [29], and Zhou et al [31], the estimated effect of air pollution in this study is quantitatively different from that reported in previous studies. Particularly, the estimated negative impact is much stronger than that reported by Liu et al [16] and Xu et al [29], who also took PM 2.5 as the indicator of air pollution. Since this study utilized a sample covering almost all Chinese regions and focused on recent years, the results may better reflect the general situation in China in the recent period.…”
Section: Discussionsupporting
confidence: 74%
See 3 more Smart Citations
“…Although the core finding of this study on the harmful influence of air pollution in China is qualitatively consistent with the findings of Dong et al [27], Xu et al [29], and Zhou et al [31], the estimated effect of air pollution in this study is quantitatively different from that reported in previous studies. Particularly, the estimated negative impact is much stronger than that reported by Liu et al [16] and Xu et al [29], who also took PM 2.5 as the indicator of air pollution. Since this study utilized a sample covering almost all Chinese regions and focused on recent years, the results may better reflect the general situation in China in the recent period.…”
Section: Discussionsupporting
confidence: 74%
“…Zhou et al [31] focused on Beijing City, and reported that, if PM 10 density increased by 1 µg/m 3 , inbound tourist arrivals in Beijing would decline by 0.33%. Differently from these two studies, Xu et al [29] reported that the response of inbound tourist arrivals to PM 10 pollution was not significant statistically, based on a sample covering 337 cities. However, they found that inbound tourists were sensitive to PM 2.5 pollution.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…The negative impact on society is not limited to health only. There is increasing evidence showing that bad air quality in general, and high NO 2 concentrations in particular, impact the economy, including finance [9] and tourism [10]. The present paper analyses the introduction of the first phase of an air quality control policy in the municipality of Milan, which started on 25 February 2019 and directly acts on traffic rules.…”
Section: Introductionmentioning
confidence: 99%